Dual-Beam Interferometric Study of Epitaxial Layer Thickness Based on Infrared Interferometry - Chen, Haojun (International Journal of Materials Science and Technology Studies, 2026)
To address the precise measurement of epitaxial layer thickness in silicon carbide materials, this paper constructs a dual-beam epitaxial layer thickness calculation model based on infrared interferometry. Derived from the fundamental optical principle of optical path difference, this model considers only the scenario where interference occurs due to a single reflection and transmission at the epitaxial layer-substrate interface. First, the optical path difference Δ is determined through geometric optical path analysis and Snell's law. Considering that the refractive index of the epitaxial layer is not a constant and exhibits dispersion effects, the refractive index function of the epitaxial layer is established using the Cauchy dispersion formula. Subsequently, under the condition of half-wave loss, the effective optical path difference formula is derived by calculating the optical path differences of reflected light 1 and reflected light 2. By combining the constructive interference condition with the effective optical path difference formula, a quantitative relationship was ultimately derived between the epitaxial layer thickness and the interference order, wave number, incident angle, and refractive index. This model provides a rigorous mathematical framework for establishing fundamental geometric relationships and incorporating dispersion characteristics in epitaxial layer thickness measurements.